2021
DOI: 10.1101/2021.03.10.21253291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monitoring the propagation of SARS CoV2 variants by tracking identified mutation in wastewater using specific RT-qPCR

Abstract: Since the end of 2020, the COVID-19 pandemic has experienced a major turning point with the appearance and rapid spread of new variants, causing a significant increase in the number of new cases requiring hospitalization. These so-called UK, South African or Brazilian variants are characterized by combinations of mutations which allow them to be distinguished from the variants which have circulated since the start of the epidemic. The impact of these variants on the functioning of healthcare systems requires m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
(13 reference statements)
0
22
1
1
Order By: Relevance
“…Besides testing the untreated wastewater, we also quantified SARS-CoV-2 RNA in 8 samples of treated wastewater (four sampling weeks from both WWTP), which gave negative results for both plants (data not shown). This is in contrast with some recent studies that reported the detection of SARS-CoV-2 RNA by RT-qPCR in treated wastewaters and even in rivers (Nasseri et al, 2021;Rimoldi et al, 2020;Wurtzer et al, 2021Wurtzer et al, , 2020, although near the quantification limits. These findings could be important to indicate if the wastewater treatment technologies are being efficient in the removal of SARS-CoV-2 and could provide a comprehensive view on the fate of SARS-CoV-2 along the entire chain of WWTPs.…”
Section: Sars-cov-2 Detection In Liquid and Solid Wastewater Fractionscontrasting
confidence: 99%
“…Besides testing the untreated wastewater, we also quantified SARS-CoV-2 RNA in 8 samples of treated wastewater (four sampling weeks from both WWTP), which gave negative results for both plants (data not shown). This is in contrast with some recent studies that reported the detection of SARS-CoV-2 RNA by RT-qPCR in treated wastewaters and even in rivers (Nasseri et al, 2021;Rimoldi et al, 2020;Wurtzer et al, 2021Wurtzer et al, , 2020, although near the quantification limits. These findings could be important to indicate if the wastewater treatment technologies are being efficient in the removal of SARS-CoV-2 and could provide a comprehensive view on the fate of SARS-CoV-2 along the entire chain of WWTPs.…”
Section: Sars-cov-2 Detection In Liquid and Solid Wastewater Fractionscontrasting
confidence: 99%
“…Most of these groups developed assays targeting only a single site for detection of each VOC lineage. They reported substantially lower sensitivity for their assays in comparison to the US CDC N1 and N2 assays and had poor amplification efficiencies (Graber et al, 2021, Wurtzer et al, 2021, Yaniv et al, 2021. A number of biomedical companies have also released products for the detection of SARS-CoV-2 VOCs in wastewater, but have not divulged additional details on their methods.…”
Section: Discussionmentioning
confidence: 99%
“…This method, constrained by the same bottlenecks of cost and infrastructure requirement as clinical sequencing, is further hampered by challenges in detection of low-frequency variants and is poorly quantitative due to the lack of robust modelling to quantify variant titers (Fuqua et al, 2021;Van Poelvoorde et al, 2021) . RT-qPCR-based methods have been developed for variant identification in clinical samples (Clark et al, 2021;Vogels et al, 2021;Wang et al, 2021) Yaniv et al, 2021aYaniv et al, , 2021bWurtzer et al, 2021 ). While RT-qPCR methods cannot discover new variants or identify variants beyond what they are designed for, they are more sensitive and quantitative, providing a readout from sample to data, in just hours.…”
Section: Introductionmentioning
confidence: 99%
“…RT-qPCR-based methods have been developed for variant identification in clinical samples (Clark et al, 2021;Vogels et al, 2021;Wang et al, 2021) but are not yet validated for quantification of variant mixtures, which are expected in wastewater samples. This motivates the development of specialized methods for quantification of variant mixtures in environmental samples such as wastewater (Graber et al, 2021;Yaniv et al, 2021aYaniv et al, , 2021bWurtzer et al, 2021 ). While RT-qPCR methods cannot discover new variants or identify variants beyond what they are designed for, they are more sensitive and quantitative, providing a readout from sample to data, in just hours.…”
Section: Introductionmentioning
confidence: 99%